Peningkatan Hasil Belajar Keterampilan Tendangan Sabit Pencak Silat Peserta Didik Fase C Melalui Model Problem Based Learning - Syayyadi, Achmad; Rahman, Taufik; Nuraisyah, Winda (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to determine the achievement of learning outcomes for crescent kick skills in pencak silat through the application of the model.Problem Based Learningfor PHASE C students (grade 6)SDN Romben Rana 571, Dungkek District, Sumenep Regencyacademic year 2024–2025. The method used isclassroom action researchwith a cycle approach that includes the stages of observation and reflection. Based on the results of the analysis at the pre-cycle stage or initial observation, it is known that only 6 out of 16 students (38%) achieved completion, while 10 students (63%) have not completed. In cycle 1 there was an increase, where 12 students (75%) achieved completion and 4 students (25%) had not. Then in cycle 2, learning outcomes showed a very significant increase, with all students (100%) successfully achieving completion. From these findings it can be concluded that the implementation ofmodel Problem Based Learningeffective in improving learning outcomes of straight kick skills in pencak silat.